Higher compliance with the enhanced recovery after surgery protocol improves postoperative recovery and 6-month mortality in upper gastrointestinal surgery - Thammawat Parakonthun; Gritin Gonggetyai; Chawisa Nampoolsuksan; Tharathorn Suwatthanarak; Thikhamporn Tawantanakorn; Jirawat Swangsri; Asada Methasate (Surgery in Practice and Science)
Introduction: The enhanced recovery after surgery (ERAS) protocol has been proven to accelerate recovery without increasing morbidity, but few data are available from developing countries. We aimed to demonstrate the correlation between compliance with the ERAS protocol and short-term outcomes in upper gastrointestinal (UGI) surgery. Materials and Methods: Patients that underwent esophageal and gastric surgeries during March 2019 to June 2021 were prospectively enrolled in this nonrandomized cohort study. The ERAS protocol was applied based on patient-doctor agreement. Patients were categorized into conventional care (CC), moderate-compliance (MC), and high-compliance (HC) groups. Short-term outcomes including gastrointestinal (GI) function recovery, length of hospital stay (LOS), postoperative complications and mortality rate were compared. Results: 158 patients were enrolled: 58 in the CC, 33 in the MC, and 67 in the HC group. The HC group demonstrated reduced time to tolerate oral diet (8 vs 7 vs 3 days; p = 0.034), recovery of GI function (72 vs 96 vs 61 h; p = 0.001) and median LOS (12.5 vs 10 vs 6 days; p < 0.001). Postoperative overall (p = 0.08) and major complications (p = 0.09) were not significantly different. Non-surgical complications were lower in the HC group (31.0 % vs 54.5 % vs 25.4 %; p = 0.013). The 28-day readmission rate was not different (8.6 % vs 3.0 % vs 1.5 %; p = 0.14). The 30-day postoperative mortality was not different (0 % vs 3.1 % vs 0 %; p = 0.15), but the 6-month mortality rate was significantly lower in the HC group (13.8 % vs 15.2 % vs 0 %; p < 0.001). Conclusion: The level of compliance with the ERAS protocol is associated with improved short-term postoperative outcome in UGI surgery. High compliance patients recovered faster, were discharged sooner, and had better 6-month survival.